PENGADAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) TAHUN ANGGARAN 2024 DESA PASIRBIRU KECAMATAN RANCAKALONG, KABUPATEN SUMEDANG, PROVINSI JAWA BARAT. - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Muhajirin, Muhajirin; Mutia Utami, Mutia Utami; Dewi Arita, Dewi Arita (Media Nusantara, 2023)
Complete Systematic Land Registration (PTSL) is a program that has a number of important objectives and benefits. Here are some of them: Objectives of Complete Systematic Land Registration (PTSL) Providing Legal Certainty: Complete Systematic Land Registration (PTSL) aims to provide legal certainty over land ownership. By systematically documenting land ownership, land owners can have clear evidence of their rights. Resolving Land Disputes: One of the main objectives of Complete Systematic Land Registration (PTSL) is to reduce land disputes. By having accurate data regarding land ownership, disputes that often arise due to ownership uncertainty can be avoided or resolved more easily. Supporting Economic Development : Complete Systematic Land Registration (PTSL) facilitates more efficient and productive land use. This can support economic development by encouraging investment and business development. Better Regional Planning : The Complete Systematic Land Registration (PTSL) program helps in better regional planning. The data collected can be used by the government to plan more efficient and sustainable land use. Increased Access to Financial Facilities: Legal certainty over land makes it easier for land owners to gain access to financial facilities, such as bank loans, which can be used for investment or development. Pasirbiru Village, located in Rancakalong District, Sumedang Regency, is developing PTSL for residents of Pasirbiru Village for free and quickly.